Ortodoksi Sufisme K.H. Shalih Darat - Mas’ud, Ali (ISLAMICA: Jurnal Studi Keislaman, 2012)
The subject of this paper is the orthodox nature of KH Shalih Daratâs Sufism. He is an Indonesian Muslim thinker of the 19th century. The paper argues that the man is behind the dissemination of not only Islam but also of Sufism on the Javanese island. Despite his high standing knowledge and piety however, the man is not yet known especially in the academic circle in Indonesia. It is this reason that the paper is interested in exploring his ideas and intellectual biography. The paper tries to show that Muslim community during his lifetime was polarized into the elites and the laymen. K.H. Shalih Darat targeted the latter while not forgetting the former. But the most striking question would be how does his orthodox religiosity fit into the laymen and work for the elites? The paper will try to answer this question by emphasizing first that for the man, orthodoxy is a must for people of the Javanese outlook. And second, it will try show that while orthodoxy and heterodoxy are always at odds with one another, the tension between the two does bring a good implication for the course of dakwah on the island.